A current perspective on hydrogen peroxide production in honey. A review. (1st December 2020) - Brudzynski, Katrina
Highlights: Variability in H2 O2 levels results from factors that interfere with GOx kinetics. H2 O2 can be produced by non-enzymatic way via polyphenol autoxidation. GOx of microbial and plant origin may contribute to H2 O2 levels. Colloidal structure of honey is the main determinant in H2 O2 production. There is the cause-effect relationship between colloidal structure and antibacterial activity. Abstract: Hydrogen peroxide plays a key role in honey antibacterial activity. The production of H2 O2 in honey requires glucose oxidase (GOx) that oxidizes glucose to gluconolactone and reduces molecular oxygen to hydrogen peroxide. The content of GOx of honeybee origin was believed to be the main predictor of H2 O2 concentration in honey. The observed variations in H2 O2 levels among honeys questioned however the direct GOx-H2 O2 relationship and left its absence opened for exploration. Here, we evaluated principal causes underlying the imbalance in the quantitative enzyme-product relationship with respect to: (a) enzyme and the product inactivation or destruction by honey compounds; (b) non-enzymatic pathway of H2 O2 formation, and (c) a potential contribution of enzymes with GOx activity originating from nectars and microorganisms inhabiting honey. We also bring new facts on the relationship between honey colloidal structure and H2 O2 production that change our traditional understanding of honey function as antimicrobial agent.